Pengaruh Motivasi Kerja, Lingkungan Kerja dan Kompetensi terhadap KinerjaKaryawan pada Bank Jateng Cabang Pembantu Wilayah Pemalang - Henry Adhi Sulistyo; Danny Manongga (Magister Manajemen STIE Bank BPD Jateng, 2020)
The purpose of this study is to find out and analyze the relationship between work motivation and employee work performance, analyze the influence of the work environment on employeeperformance, and analyze the effect of competence on employee performance. The sample used inthis study were all employees of the Central Java Regional Government Branch Office in Pemalang,totaling 30 employees. The conclusion shows that work motivation has a positive and significanteffect on employee performance, the work environment has a positive and significant effect onemployee performance, and competence has a positive and significant effect on employeeperformance.